2006
DOI: 10.1093/alcalc/agl106
|View full text |Cite
|
Sign up to set email alerts
|

Study of Dopamine Receptors Genes Polymorphisms in Bipolar Patients With Comorbid Alcohol Abuse

Abstract: Our findings suggest that the analysed polymorphisms of the dopamine genes polymorphisms may not be involved in the shared genetic vulnerability to both, bipolar disorder, and alcohol abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…The link between dopamine receptor genes and alcohol abuse comorbid with affective disorders, for example, remains controversial and may depend on the specific type of affective disorder under study (Huang et al, 2004; Huang et al, 2007; Lin et al, 2007; Szczepankiewicz et al, 2006; Young et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…The link between dopamine receptor genes and alcohol abuse comorbid with affective disorders, for example, remains controversial and may depend on the specific type of affective disorder under study (Huang et al, 2004; Huang et al, 2007; Lin et al, 2007; Szczepankiewicz et al, 2006; Young et al, 2002). …”
Section: Resultsmentioning
confidence: 99%
“…Only a single dose level of L-Dopa was examined, and associations with the gene score might differ at higher drug doses. Some genetic polymorphisms have uncertain associations with dopaminergic signaling, and negative studies have been reported for each of the polymorphisms used in the current gene score [128], [129], [130], [131]. Dopamine effects are influenced by numerous factors such as the dynamics and concentration of its release [10], [132], issues not examined in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis of DRD1 DdeI genotypes and the Zuckerman scores, exhibited a significant association only in men, indicating a male-limited association between the DRD1 gene polymorphism and sensationseeking score in alcohol-dependent subjects (28). The same polymorphism has not shown any significant association in both the male and the female subjects analysed (29). Furthermore, this polymorphism has shown a significant association with severity and temperament of alcohol dependence in Koreans (30).…”
Section: Drd1mentioning
confidence: 99%